Improving inventory accuracy with internet of things: A case study in a manufacturing company - Charissa, Endar; Lee, Khai Loon (Penerbit Universiti Malaysia Pahang, 2023)
Inventory accuracies need to be achieved to obtain efficient inventory management for a company. The problem of the study is the gaps of inventory accuracy between the ideal and actual KPI in ABC manufacturing company. ABC manufacturing company was chosen because the company experiences issues with inventory accuracy. Thus, this study aims to analyze the inventory accuracy of ABC manufacturing company, investigate the root causes affecting inventory inaccuracy in ABC manufacturing company, and propose a technology and best practices to improve the company's inventory accuracy. The study applied a qualitative research design, in which several interviews were conducted to get the data from the company. Besides, fishbone diagram analysis (Ishikawa diagram) is used to analyze the root causes of inventory inaccuracies in ABC manufacturing company. This study reveals that inventory inaccuracy is influenced by bill of materials (BOM) errors, wrong inventory counting and inventory shrinkage. Inaccurate inventories affect the optimal function of the company supply chain and directly impact its sales activities. This study proposes implementing a smart antenna in a radio frequency identification (RFID) scanner in improving inventory accuracy. This will be the best option for ABC manufacturing company because the finished products from the site of the operations are transported across the road through a conveyor bridge into the finished goods warehouse. A smart antenna RFID reader can provide a greater coverage area for each cell site.